The Validity and Reliability of Subjective Well-Being Instruments in Early Adolescents - Sunarsih Sunarsih; Farida Harahap; Habibullah Habibullah; Muslim Afandi (Humaniora, 2020)
The research aimed to produce empirical evidence about the validity and reliability of subjective well-being instruments by modifying the instruments. The research’s subjects were 394 early adolescent respondents ranging in age from 12-13 years old in Sleman regency, Yogyakarta, using a random sampling technique. The validity of subjective well-being instruments was measured by using expert judgment and calculating Gregory’s formula. Instrument reliability was measured by Cronbach’s Alpha calculation. The results show that the subjective wellbeing instrument in the modified early adolescents has good validity and reliability so that the modification of this instrument can be used to measure the condition of subjective well-being in early adolescents in Indonesia.